Inverse Electron Demand Diels−Alder Reactivity and Electrochemistry of New Tetrazine Derivatives. Issue 2 (11th January 2017) - Li, Yuan; Miomandre, Fabien; Clavier, Gilles; Galmiche, Laurent; Alain‐Rizzo, Valérie; Audebert, Pierre
Abstract: New tetrazine derivatives were prepared and their electrochemical properties as well as their reactivity in the inverse demand Diels−Alder (DAinv) reaction were investigated. DFT calculations were performed to calculate the energy and electronic distribution in the frontier molecular orbitals. In particular, the reactivity of these tetrazine derivatives has been compared with that of the already known dichlorotetrazine. A comparison of the gathered data allows a rough correlation to be established between the reactivity and the electron‐withdrawing character of the substituent, but only a closer examination of the involved orbitals can enable an accurate prediction of the DAinv reactivity of the investigated compounds. Abstract : Inverse demand : New tetrazine derivatives are prepared and their electrochemical properties as well as their reactivity in the inverse demand Diels−Alder reaction are investigated. DFT calculations are performed to calculate the energy and electronic distribution in the frontier molecular orbitals. A comparison of the data allows a rough correlation to be established between the reactivity and the electron‐withdrawing character of the substituent.